2019
DOI: 10.1590/1676-0611-bn-2018-0651
|View full text |Cite
|
Sign up to set email alerts
|

Specimens inventory of Tabanidae (Diptera) of Entomological Collection of National Museum of Natural History - Universidade Federal do Rio de Janeiro

Abstract: A checklist of tabanids of the Entomological Collection of National Museum of Natural History - Universidade Federal do Rio de Janeiro is provide. A total of 5,325 specimens was examined of which 2,916 were found identified, belonging to 341 species, 42 genera e four varieties, collected from all continents since 1902. The currently taxa names were provided when possible, also currently localities of collections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Thereby, results reported here that most (92.86%) foals remain seronegative to this virus despite remaining with their EIAV seropositive mares throughout the entire weaning process suggest that implementation of such policies is not an absolute requirement for restorative breeding programs. Moreover, in contrast to conditions outlined above in work conducted in the United States [20], equids in this study were feral, living in an environment where EIAV is endemic and where the hot, humid tropical rainforest climate support very high insect vector populations all year round [17,20,37].…”
Section: Discussionmentioning
confidence: 75%
“…Thereby, results reported here that most (92.86%) foals remain seronegative to this virus despite remaining with their EIAV seropositive mares throughout the entire weaning process suggest that implementation of such policies is not an absolute requirement for restorative breeding programs. Moreover, in contrast to conditions outlined above in work conducted in the United States [20], equids in this study were feral, living in an environment where EIAV is endemic and where the hot, humid tropical rainforest climate support very high insect vector populations all year round [17,20,37].…”
Section: Discussionmentioning
confidence: 75%
“…In this current study it is shown that 24 of 26 (92.86%) foals born to EIAV seropositive mares remained seronegative to this virus even staying a long period with their respective EIAV-seropositive mothers, in the case of all but 2 Group A subjects, over 2 years. This is despite living a feral existence, unlike the animals described by McConnico et al (2000), in an environment where EIAV is endemic and the hot, humid tropical rainforest climate supports very high insect vector populations all year round [14,18,35].…”
Section: Discussionmentioning
confidence: 97%